Effect of progesterone coated nano fibre dermal patch (ProSync-NF) on cattle diagnosed with Anestrus and silent or unobserved estrus - LAKSHMIKANTAN, U; VADIVOO, V S; GEETHA, T; MATHIVANAN, R (The Indian Journal of Animal Sciences, 2021)
Transdermal Progesterone therapy for the treatment of True and False anestrus was evaluated by using the product ProSync-nano fibre (NF) dermal patch. Eighteen (N = 18) randomly selected animals from different dairy farms during the farm visit by this centre were used for the study. The animals which were reported to be not exhibiting estrus signs even after prolonged postpartum period were designated into three groups. Group I (n = 7) had no palpable ovarian structures treated with ProSync-NF alone, Group II (n = 9) had corpus luteum, treated with ProSync-NF + PGF2 and Group III (n = 2) animals were diagnosed as having cyst were also treated with ProSync-NF + PGF2. Group III animals which were diagnosed with cystic condition did not respond to ProSync-NF therapy. Out of eighteen animals totally used in this study fifteen (83.3%) animals evinced estrus after the treatment with ProSync-NF. Out of fifteen, nine (60%) and six (40%) animals showed estrus around 3 days (72 h) and 5 days (120 h) after dermal patch removal. Overall, out of the 18 animals treated with ‘ProSync–NF’ dermal patch, ten cows (55.5%) conceived which indicates fertile estrus induction at the first service. Moreover, the clinical problem like vaginitis would not occur when using dermal route Progesterone therapy. Hence it could be concluded that ‘ProSync-NF’ dermal patch could be effectively used to induce estrus in anestrus cows.